Associations between parenting strategies and BMI percentile among Latino children and youth with intellectual and developmental disabilities - Magaña, Sandy; Errisuriz, Vanessa L.; Yu, Amy Pei-Lung; Heydaria, Nazanin; Zeng, Weiwen; Mirza, Mansha; Vanegas, Sandra; Brown, Stephany; Parra-Medina, Deborah; Suarez-Balcazar, Yolanda (Frontiers in Pediatrics, 2023)
Introduction Maintaining healthy weight is a challenge for all children, and particularly for children with IDD compared to nondisabled children and for Latino children compared to non-Latino White children. Parenting practices related to food intake and physical activity have been found to be important in maintaining children's weight. In this study, we describe the prevalence of overweight and obesity status among Latino children with IDD and their maternal caregivers and determine the relationship between food and physical activity parenting practices and childhood obesity among Latino children with IDD. Methods We interviewed 94 Latino parent/child dyads and collected information about parenting practices, home environment, and parent and child height and weight using standardized measures. Parent body mass index (BMI) and child BMI percentile were calculated from height and weight. Results The combined overweight/obesity status for children in our sample was high (60.3%) compared to national rates among nondisabled Latino children (56%) and non-Latino White children with autism (37%). Contrary to research on nondisabled children, we found that greater parental use of controlling dietary strategies was associated with lower BMI percentile in Latino children with IDD. These findings may be indicative of the fact that children with IDD tend to have unique dietary behaviors that warrant more disability and culturally sensitive strategies. Discussion Our findings suggest that overweight and obesity is especially prevalent for Latino children with IDD and that more research is needed on family factors that promote health in Latino families of children with IDD.